Pemeriksaan kesehatan pada Kelompok Adat Terpencil Suku Anak Dalam di Sungai Terap - Sari, Lisa Anita (Jurnal Pengabdian Harapan Ibu (JPHI), 2024)
Efforts to improve public health in remote indigenous communities continue to be increased. This is because they are often an inaccessible part of the government's attention, especially regarding their health conditions. Their residence is far from local residential areas, their frequent hunting in the forest and their habit of moving frequently make it difficult for local health center officials to provide health services. Therefore, the Professional Organization (OP) of the Indonesian National Nurses Association (PPNI) of Jambi Province together with the Durian Luncuk Community Health Center carried out community service in the form of health checks and treatment for the Suku Anak Dalam (SAD) in Sungai Terap, Batanghari Regency. This activity shows that SAD suffer from common health problems such as coughs and colds that affect their children. This will certainly have an impact on their immune system which may decrease at any time and also discomfort in the throat which affects their appetite so that nutritional intake becomes less. SAD still likes to move around, so every time the community health center officers make a residential visit, they rarely meet the same individual. From the results of this community service, it was found that it is important to carry out regular and routine health checks and not only rely on local health center officers to do it, but wider community awareness, such as health education institutions, also needs to participate.